"Every method seems to have its problems"- Perspectives on side effects of hormonal contraceptives in Morogoro Region, Tanzania. Issue 1 (December 2015) - Chebet, Joy; McMahon, Shannon; Greenspan, Jesse; Mosha, Idda; Callaghan-Koru, Jennifer; Killewo, Japhet; Baqui, Abdullah; Winch, Peter
Abstract Background Family planning has been shown to be an effective intervention for promoting maternal, newborn and child health. Despite family planning's multiple benefits,  women's experiences of - or concerns related to - side effects present a formidable barrier to the sustained use of contraceptives, particularly in the postpartum period. This paper presents perspectives of postpartum, rural, Tanzanian women, their partners, public opinion leaders and community and health facility providers related to side effects associated with contraceptive use. Methods Qualitative interviews were conducted with postpartum women (n  = 34), their partners (n  = 23), community leaders (n  = 12) and health providers based in both facilities (n  = 12) and communities (n  = 19) across Morogoro Region, Tanzania. Following data collection, digitally recorded data were transcribed, translated and coded using thematic analysis. Results Respondents described family planning positively due to the health and economic benefits associated with limiting and spacing births. However, side effects were consistently cited as a reason that women and their partners choose to forgo family planning altogether, discontinue methods, switch methods or use methods in an intermittent (and ineffective) manner. Respondents detailed side effects including excessive menstrual bleeding, missed menses, weight gain and fatigue. Women, their partners and community leaders also described concerns that contraceptives could induce sterility in women, or harm breastfeeding children via contamination of breast milk. Use of family planning during the postpartum period was viewed as particularly detrimental to a newborn's health in the first months of life. Conclusions To meet Tanzania's national target of increasing contraceptive use from 34 to 60 % by 2015, appropriate counseling and dialogue on contraceptive side effects that speaks to pressing concerns outlined by women, their partners, communities and service providers are needed.